The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fmicb.2022.1092184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different phosphate sources on uranium biomineralization by the Microbacterium sp. Be9 strain: A multidisciplinary approach study

Abstract: IntroductionIndustrial activities related with the uranium industry are known to generate hazardous waste which must be managed adequately. Amongst the remediation activities available, eco-friendly strategies based on microbial activity have been investigated in depth in the last decades and biomineralization-based methods, mediated by microbial enzymes (e.g., phosphatase), have been proposed as a promising approach. However, the presence of different forms of phosphates in these environments plays a complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Such modifications can lead to changes in the oxidation state of some radionuclides, affecting their solubility and mobility through the repositories. However, microorganisms can directly influence the mobility of radionuclides and other elements through different processes such as intracellular accumulation, biotransformation (redox reactions) biosorption, or biomineralization ( Shukla et al, 2017 ; Lopez-Fernandez et al, 2020 ; Ruiz-Fresneda et al, 2020a ; Martinez-Rodriguez et al, 2022 ; Figure 4 ).…”
Section: Diversity and Influence Of Microorganisms In Dgr Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such modifications can lead to changes in the oxidation state of some radionuclides, affecting their solubility and mobility through the repositories. However, microorganisms can directly influence the mobility of radionuclides and other elements through different processes such as intracellular accumulation, biotransformation (redox reactions) biosorption, or biomineralization ( Shukla et al, 2017 ; Lopez-Fernandez et al, 2020 ; Ruiz-Fresneda et al, 2020a ; Martinez-Rodriguez et al, 2022 ; Figure 4 ).…”
Section: Diversity and Influence Of Microorganisms In Dgr Systemsmentioning
confidence: 99%
“…These results confirm the capacity of these bacteria to biomineralize uranium, which had been enhanced by the G2P amendment through phosphatase activity. In the study of Martinez-Rodriguez et al (2022) Microbacterium sp. Be9 strain was used, previously isolated from U-mill tailings and determined that the U-biomineralization process was dependent on the type of phosphate source.…”
Section: Interaction Mechanisms Between Microorganisms and Relevant R...mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been discovered that the naturally generated protein polymers Bombyx mori silk fibroin may guide the regulated mineralization of diverse nanomaterials because of its distinctive self-assembly behavior, high cytocompatibility, and biomechanical capabilities. In order to create more efficient lithium (Li-ion) cells, Martínez-Rodríguez et al [15] used a biomineralization approach based on the effective framework of silk proteins to create hierarchical olive-like organized magnetite and carbon nanomaterials. Cai and Larese-Casanova [16] also showed that they could use this method to make electrocatalyst for high-performance Li-ion batteries.…”
Section: Peptide Monomersmentioning
confidence: 99%